Agroecologia e sua epistemologia - Borsatto, Ricardo Serra; Do Carmo, Maristela Simoes [UNESP] (Interciencia, 2012)
In the scope of this work Agroecology is considered as a science that demands and seeks a different epistemology from that used by conventional science in order to build its methodological approaches. Within this context, this paper presents the results of a theoretical effort to systematize the state of the art of the debate on this subject. It establishes that Agroecology requires a transdisciplinary approach to deal with the socio-environmental crisis currently experienced in the rural environment. At the end, it is indicated that the theory of complex thinking, proposed by Edgar Morin, can constitute an interesting philosophical framework wherein Agroecology can be based with the aim of establishing a new paradigm for addressing rural areas.
Agroecology's epistemology
La agroecologia y su epistemologia